IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER PADA PESERTA DIDIK DI SMA NEGERI 3 TAKALAR - Nur, Muhammad; Arsyad, Azhar; Alang, Sattu; Shabir U, Muhammad (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The aim of this research is to explore the implementation of character education values at SMA Negeri 3 Takalar. This research is qualitative research using a phenomenological approach. Data sources were obtained through islamic spiritual development teachers, scout leaders, paskibraka leaders, arts and culture coaches, school principals and vice principals of curriculum, as well as students as the main subject. Data collection techniques were carried out through interviews and observation. Data validity techniques use triangulation of sources and techniques. The results of this research show that the character education values applied at SMA Negeri 3 Takalar in learning are religious values, nationalist values, independence values, mutual cooperation values and integrity values. The application of character values in islamic learning is reflected in extracurricular activities, such as islamic spiritual activities (rohis), paskibaraka, scouts, and art studios. From this activity, it can be seen that students have an increasing attitude of discipline, cooperation, perseverance, responsibility, and religious attitudes. Character formation is carried out through habituation shown by extracurricular coaches together with staff and the Head of SMA Negeri 3 Takalar. The habits in question are discipline, cooperation, perseverance, responsibility and religious values, so that students have good morals, both in the school environment, family environment and community environment.